Cerebral palsy and neonatal death in term singletons born small for gestational age. - Stoknes, M; Andersen, G; Dahlseng, M; Skranes, J; Salvesen, K; Irgens, L; Kurinczuk, J; Vik, T (2012)
BACKGROUND AND OBJECTIVES: To investigate the probable timing of events leading to cerebral palsy (CP) in singletons born small for gestational age (SGA) at term, taking neonatal death into consideration. METHODS: In this registry-based cohort study, data on 400 488 singletons born during 1996-2003 were abstracted from the Medical Birth and the CP registries of Norway. Among 36 604 SGA children (birth weight <10th percentile), 104 died in the neonatal period and 69 developed CP. Apgar scores at 5 minutes, risk factors, MRI findings, and CP subtypes were used to assess the timing of events leading to CP or neonatal death. RESULTS: Intrapartum origin of CP was considered in 5 SGA children (7%; 95% confidence interval: 3-16) in comparison with 31 of 263 (12%; 95% confidence interval: 8-16) non-SGA children (P = .28). The proportions of children who died in the neonatal period after a probable intrapartum event did not differ between the groups when children with congenital malformations were excluded. Probable antenatal events leading to CP and neonatal death were more common among SGA than non-SGA children (P < .001). CONCLUSIONS: In ~90% of children born SGA the event leading to CP is of probable antenatal origin. The low proportion of SGA children with CP after a probable intrapartum event was not outweighed by a higher neonatal mortality rate when congenital malformations were excluded. The higher risk of CP among SGA than among non-SGA children is probably due to a higher prevalence of antenatal risk factors.